2011
DOI: 10.1080/10942910903453389
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition andTransFatty Acids in Crisps and Cakes in Turkey's Markets

Abstract: In this study, trans fatty acid and fatty acid composition of 57 crisps and 50 cakes sold in the markets in Turkey were determined. C 18:1, oleic acid, was the major fatty acid in all crisps and cake samples. The percentages of saturated fatty acids (SFAs), monounsaturated fatty acids (MUFAs), and polyunsaturated fatty acids (PUFAs) ranged between 27.98-46.57, 35.73-47.57, and 9.86-35.90 g/100 g fatty acids in crisps and 35.41-54.03, 25.89-44.87, and 10.52-26.97 g/100 g fatty acids in cakes, respectively. Tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
3
7
1
Order By: Relevance
“…These authors also concluded that unpackaged bakery products had higher amounts of TFA compared to packaged ones, as observed in the present study. Similar results were found outside Europe, namely for margarines and table spreads in New Zealand, with up to 14.5% TFA ( Saunders et al., 2008 ) or in Turkey, where TFA content in cakes ranged from 0.0% to 5.1% in the fat ( Cakmak et al., 2011 ). However, several improvements have already been recognized in some countries, as for the generally low TFA in Spanish industrial pastry, as published by Ansorena et al.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…These authors also concluded that unpackaged bakery products had higher amounts of TFA compared to packaged ones, as observed in the present study. Similar results were found outside Europe, namely for margarines and table spreads in New Zealand, with up to 14.5% TFA ( Saunders et al., 2008 ) or in Turkey, where TFA content in cakes ranged from 0.0% to 5.1% in the fat ( Cakmak et al., 2011 ). However, several improvements have already been recognized in some countries, as for the generally low TFA in Spanish industrial pastry, as published by Ansorena et al.…”
Section: Resultssupporting
confidence: 73%
“…In the absence of a representative national nutrition survey, with ingestion patterns and relative contributions to fat consumption, a preliminary desk review was performed on literature data, aiming to identify the food categories with potentially higher amounts of TFA from industrial origin in other countries ( Hulshof et al., 1999 , Chiara et al., 2003 , Craig-Schmidt, 2006 , Stender et al., 2006 , Baylin et al., 2007 , Ledoux et al., 2007 , Griguol et al., 2007 , Wagner et al., 2008 , Richter et al., 2009 , Fritsche et al., 2010 , Remig et al., 2010 , Cakmak et al., 2011 ; Hissanaga et al., 2012 , Roe et al., 2013 , Saunders et al., 2008 ). The following food categories were selected: bakery/breakfast cereals, biscuits/wafers/cookies, bouillon cubes, butter, chocolate snacks, chocolate spreads, fast food, instant desserts, instant soups, margarines/shortenings, pastry, popcorn, and potato chips/French fries.…”
Section: Methodsmentioning
confidence: 99%
“…The second saturated fatty acid predominantly from P1-P6 chips samples, was stearic acid (C18:0), with values ranging from 1.303% (P3) to 4.373% (P4). Our results are in accordance with the ones obtained in the study of Cakmak et al (2011) [19], where palmitic acid was the predominant fatty acid in the potato crisps samples, the value ranging from 24.03 to 40.12 g/100 g fatty acids, followed by stearic acid with a mean value of 4.52 g/100 g fatty acids. Similar results were also obtained in the study of Fu et al (2008) [30] on potato chips and in the study of Fernandez and Juan (2000) [31] on fried potatoes, where palmitic and stearic acids were the predominant SFA.…”
Section: The Fat Content Fatty Acids (Fai) and Trans Fatty Acids (T-supporting
confidence: 92%
“…These results are comparable to those reported by Cakmak et. (2011) [19] who found in potato crisps a TFA content ranged from 0.02 to 1.35 g/100 g fatty acids, with a mean value of 0.37 g/100 g fatty acids, of which, elaidic acid (C18:1n9t) had values ranging from 0 to 0.93 g/100 g fatty acids. In the study of Costa et al (2016) [15], the TFA content of the potato chips and French fries analyzed was higher than the values of the present study but less than 2 g/100 g fat.…”
Section: The Fat Content Fatty Acids (Fai) and Trans Fatty Acids (T-mentioning
confidence: 97%
See 1 more Smart Citation